Scientific Collaboration Network in Cryptocurrency Adoption Research: A Bibliometric Study - Judijanto, Loso (The Eastasouth Management and Business, 2025)
The rapid growth of cryptocurrency adoption has sparked a surge in interdisciplinary academic research, involving scholars from technology, finance, behavioral sciences, and policy studies. This study investigates the structure and dynamics of scientific collaboration in cryptocurrency adoption research using a bibliometric approach. Drawing on data from the Scopus database (2011–2024), we employed VOSviewer to map co-authorship networks at the levels of individual authors, institutions, and countries. The findings reveal a moderately integrated global research landscape, with the United States, India, and China emerging as central contributors. Distinct thematic clusters reflect disciplinary orientations—ranging from blockchain infrastructure to financial market implications and user acceptance models—though cross-cluster collaboration remains limited. Institutional and regional analyses show growing contributions from South and Southeast Asia, yet highlight the underrepresentation of Africa and Latin America. The study underscores the importance of fostering more inclusive, interdisciplinary, and transnational collaborations to advance a comprehensive understanding of cryptocurrency adoption in diverse socio-economic contexts.